A reforma de ensino pela lei nº 5.692/71 e as mudanças da inspeção escolar em Minas Gerais - Carvalho, Paulo Leandro De (2020)
School Inspection in Minas Gerais is a function that started incipiently in the mid1830s, in the 19th century and follows the changes that took place in Minas Gerais education. This research intends to reconstruct the trajectory of the work of inspectors in Minas Gerais, in order to understand the changes and permanences in the organization and functioning of the School Inspection, especially after the implementation of the 1971 Teaching Reform. We problematize the prescriptive contours that the Secretary of Education State of Education sought to establish about the role of inspectors and the strategies for implementing a new school inspection profile. The research is based on the norms and guidelines on School Inspection produced by the Minas Gerais State Department of Education (SEE) and the State Education Council (CEE) and documents related to courses and meetings of School Inspectors promoted by SEE, the from the implementation of the Teaching Reform of 1971. Although the sources indicated that an attempt was made to give a pedagogical emphasis to the inspection work, throughout the period analyzed, the inspection legislation in Minas Gerais revealed that the inspector was considered the communication channel between teaching bodies: central body, teaching police stations and school units and responsible for ensuring compliance with state regulations. When dealing with the reconfiguration of inspection in Minas Gerais based on legislation that regulated the function and documentation of courses and meetings, promoted in the 1970s, we identified four moments of this change in school inspection in the state.